O drama como método de investigação de linguagem: uma interpretação do dramatismo de Kenneth Burke - Gonzaga, Deusimar (2015)
This study aims at presenting and discussing some of the aspects of dramatism, method of analysis of human relations and mainly of the acts of the language and of the thinking, as it is presented by the North American philosopher and literary critic Kenneth Burke (1897-1993), from the years 1930 to 1960. Practically unknown in our language, Kenneth Burke‟s name and of his dramatism are compulsory presences in the recent compendiums which deal with the studies of performance and of cultural performances, for the comparison and the relation they establish between everyday life and the drama and thus require be better known. Among many theorists, Burke‟s works have influenced the literary critics Harold Bloom (1930) and Susan Sontag (1933-2004), his student at the University of Chicago, and mainly the theoretical founding of the sociologist Erving Goffman (1922-1982), being that in his studies of everyday life as well as in his “dramaturgical approach”. As it is implied from dramatism, we are not only language users, we are also used by it and language determines our actions. Dramatism is established as an instrument of analysis of language as symbolic action from five key terms (dramatistic pentad): the act in itself, what has been done; the agent of the act, the actor, who performed the act; the scene (the place, the where); the agency, the means/instruments or how the action is performed, or even the autonomous capability of people to make their own choices; and the purpose. The act is the central term around which the five categories of analyses are organized (pentad) and the investigation of the motives of the action is the fundamental strategy of the dramatistic analyses. Burke proposes that the field of observation of the human action and of its innumerable combinations, the transpositions and the transformations among the terms of the cited pentad, makes it possible for an analysis of the human action that has drama as its central term. Dramatism attempts to answer the questions of how human actions can be explained, and mainly how these actions are determined by the symbolic capability. Dramatism becomes a central element in the analysis of human theatricality, of the human being in performance.